Taxonomy of Anotylus nitidifrons group (Coleoptera: Staphylinidae: Oxytelinae) and five new species from China - Wang, Lin-Fei; Zhou, Hong-Zhang (Zootaxa, 2020)
The Anotylus nitidifrons group (Coleoptera: Staphylinidae: Oxytelinae) is studied and five new species are described from China: Anotylus sculptifrons Wang & Zhou, sp. nov. (Hubei, Yunnan), A. corrugifrons Wang & Zhou, sp. nov. (Guangxi), A. applanatifrons Wang & Zhou, sp. nov. (Zhejiang), A. declivisculptilis Wang & Zhou, sp. nov. (Guangxi), A. scabrifrons Wang & Zhou, sp. nov. (Sichuan). The taxonomic history of Anotylus nitidifrons group is briefly reviewed and another Chinese species is redescribed. Color plates and line-drawing are provided for all new species and other two species known from China. A key to the Chinese species of Anotylus nitidifrons group is included in the paper.